2020
DOI: 10.1111/all.14625
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate as a bioactive human milk protective component against food allergy

Abstract: Background: Food allergy (FA) is a growing health problem worldwide. Effective strategies are advocated to limit the disease burden. Human milk (HM) could be considered as a protective factor against FA, but its mechanisms remain unclear. Butyrate is a gut microbiota-derived metabolite able to exert several immunomodulatory functions. We aimed to define the butyrate concentration in HM, and to see whether the butyrate concentration detected in HM is able to modulate the mechanisms of immune tolerance.Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 85 publications
(201 reference statements)
2
65
0
Order By: Relevance
“…Indeed, human milk fat is high in unsaturated fatty acids and PUFAs, particularly the essential fatty acids LA and ALA. The beneficial effects of human milk also depend on its bioactive/immunomodulatory factors (oligosaccharides, lactose, glycosaminoglycans) [ 61 ]. The World Health Organization recommends the exclusive breastfeeding of infants for the first 6 months of age, since maternal milk reduces the incidence of neonatal necrotizing enterocolitis, gastroenteritis, respiratory infection, and immunologically based disease, and improves later cognitive development [ 62 , 63 ].…”
Section: Milk Fatty Acid Composition In Different Animal Speciesmentioning
confidence: 99%
“…Indeed, human milk fat is high in unsaturated fatty acids and PUFAs, particularly the essential fatty acids LA and ALA. The beneficial effects of human milk also depend on its bioactive/immunomodulatory factors (oligosaccharides, lactose, glycosaminoglycans) [ 61 ]. The World Health Organization recommends the exclusive breastfeeding of infants for the first 6 months of age, since maternal milk reduces the incidence of neonatal necrotizing enterocolitis, gastroenteritis, respiratory infection, and immunologically based disease, and improves later cognitive development [ 62 , 63 ].…”
Section: Milk Fatty Acid Composition In Different Animal Speciesmentioning
confidence: 99%
“…Interestingly, butyrate is the only SCFA produced exclusively by microbial gut fermentation, while other SCFAs are affected by host metabolism [10]. Recent findings support the hypothesis that butyrate might contribute to the development of immune oral tolerance and in the prevention and treatment of food allergies [11][12][13]. This review summarizes what is currently known about the role of butyrate in food allergies, underlining the complex interplay among early life nutrition, gut microbiome, and immune system.…”
Section: Introductionmentioning
confidence: 82%
“…In peripheral blood mononuclear cells (PBMCs) from children with food allergy, butyrate enhanced IL-10, IFN-γ, and Forkhead box P3 (FOXP3) expression through epigenetic mechanisms. Moreover, it promoted dendritic cells, regulatory T cells (Tregs), and the precursors of M2 macrophages [11]. The authors concluded that an effective concentration of butyrate in human milk could contribute to explain the protective role of breastfeeding against food allergy.…”
Section: Breastfeeding: Butyrate As Bioactive Human Milk Protective Component Against Food Allergymentioning
confidence: 99%
See 2 more Smart Citations